Avaliação da influência da estrutura física das unidades de internação de clínica médica e cirúrgica de um hospital público de grande porte do município de são paulo: proposta para o gerenciamento de risco de quedas - Menezes, Maria Aparecida Jesus (2015)
To understand the relationship between falls and environmental hazards is necessary to identify the hazards of the environment that may influence the occurrence of these events. The aim of this work is to identify risks associated with the physical structure in patient units of medical and surgical clinics of a public hospital in the city of São Paulo. To evaluate the influence in the fall of hospitalized patients, identifying existing security measures, providing support for the design and construction phases of actions aimed at improving the management of the risk of falling. This is a descriptive study / exploratory case study. The technique of data collection used was a survey, through script's characteristic being listed spaces for the accommodation of patients and plant units. We were selected 06 units in the period January-June 2014.The notifications was 205 falls during this period. The results, the average age of individuals fall victims was 57 years and there was no difference between men and women. The mean time from admission until the occurrence was 14 days. A predominance of falls among men (59%) and at night (50%). 43% occurred in the fourth and 24% in the bathroom, totaling 67% of occurrences. The 6 units assessed, 100% meet the requirements that are minimum dimensions per room / bed, exclusive bathroom for each room, grab bars near the toilet, nurse call system and dry conditions in all rooms at the time of observation. Grab bars in the box in all bathrooms, wake lighting in all rooms, fluorescent general lighting in all rooms and nursing signaling items are served in most units (84%). The criteria light switch accessible and furniture with trundle and locks in all rooms are not seen in 100% of the units, which may be related to the occurrence of falls at night (50% of reported incidents). In 67% of the units had not caged beds in all beds, beds with locks on all beds, electric beds on all beds and stair steps in this 2 all beds and rubber tip. It follows that the physical structure can be evaluated as influential in determining the occurrence of falls from other environmental factors are considered. The scales should not be composed only with information about dimensions, but assess how hospital organizations use available space. The descriptives and technical specifications for equipment and furnishings should be updated and health services should ensure the proper performance of devices and availability to users.